Abnormality of Soft Tissue in the Oral Cavity of Youth with Normal Blood Pressure and Hypertension During Social Service Activities in Karang Pilang District - Kharinna widowati; Isidora Karsini S; Aulia Dwi Maharani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2022)
Background: The oral mucosa soft tissue can develop white, red lesions, vesiculobullous lesions, and ulcerated lesions as a result of systemic disease. The age of patients with systemic diseases affects the profile of oral soft tissue abnormalities. In developed countries, roughly 60% of young people with systemic diseases have at least one oral lesion. Hypertension is one of the systemic diseases that can cause clinical manifestation in oral soft tissue mucosa. Objective: To discover the profile of soft tissue abnormalities of the oral cavity in youth with a normal blood pressure and hypertension in the Karangpilang district. Methods: The type of this research is analytical observational. The method is that blood pressure is measured in each sample, then grouped into 2 (normal blood pressure group and hypertension group). Furthermore, each group was examined with an intra-oral examination that will be carried out to determine the condition of the soft tissue of the oral cavity in each sample. Processing and analyzing the research data using the Spearmen Correlation Test method. Result: There is a strong positive relationship between the systolic pressure and the number of soft tissue abnormalities in the oral cavity. Conclusion: The oral cavity's soft tissues are frequently obtained during examinations of patients with elevated blood pressure.